Patient and Healthcare Professionals Perspectives on the Delivery of Exercise Education for Patients With Type 1 Diabetes - Litchfield, Ian; Andrews, Rob C.; Narendran, Parth; Greenfield, Sheila (Frontiers in Endocrinology, 2019)
Objective One way of improving the prognosis for the growing numbers of people with type 1 diabetes is to increase their frequency of exercise. One known barrier to this is the lack of cohesive support and information from care providers. To better understand the issues around existing support for patients wishing to exercise and inform the co-design of an education package specifically to facilitate safe exercise we interviewed care providers and patients about the existing provision of support. Research Design and Methods The study was based within two large UK teaching hospitals where iterative focus groups were undertaken consisting either of patients diagnosed with type 1 diabetes who undertook regular exercise, or with health care providers that were part of the diabetes care team. These were complemented by 1:1 interviews with those unable to attend group discussions. Results We found the successful provision of education and advice was influenced by factors relating to the individual patient and their service provider. Patient factors included the type of activity and complexity of the exercise regime, the level of engagement with their condition and care and health literacy. Service-related factors included inconsistent training, a lack of capacity and continuity and limited coherence of information from across their care team. Conclusions Any education package developed to support exercise in patients with type 1 diabetes should be offered at a time following diagnosis in accordance with patients’ preferences and priorities, contain information on how to manage regular and irregular bouts of exercise. Peer to peer monitoring was favoured and group delivery could be use to facilitate such as well as considering the content and relevance of any supporting materials. Training should also be available for staff across the care team to enable them to either deliver the course or be confident in offering salient advice as part of routine care.